Analisis Pengaruh Promosi dan Brand Image terhadap Keputusan Pembelian Paket Umroh pada Travel Al-Azhar Bukittinggi - Etika Rahma; Novera Martilova (Transformasi: Journal of Economics and Business Management, 2024)
This research is motivated by the increasing number of Umrah travel agencies. With the emergence of various travel agents in the market, consumers can choose which travel agent they want to use. This type of research uses a quantitative approach which shows how much influence promotion and brand image have on the decision to purchase Umrah packages at Al-Azhar Bukittinggi travel. This research uses primary data, namely questionnaires for pilgrims who have departed on the Al-Azhar Bukittinggi trip. The sample consisted of 81 congregations. Data collection techniques using questionnaires, observation and documentation. The data analysis techniques used are research instrument testing, classical assumption testing, determinant coefficient testing, and hypothesis testing. With a calculated t value of 5.389 > t table 1.665 and sig 0.000 < 0.05, it can be partially seen that the promotion variable has a strong positive influence on the choice of purchasing Umrah packages. The choice to purchase Umrah packages is not significantly influenced by brand image (sig value: 0.719 > 0.055). Judging from the determinant coefficient (R-Squere), the influence of brand image and promotion on purchasing decisions is 0.634. This shows that 63.4% of decisions to purchase Umrah packages at Al-Azhar Bukittinggi travel are influenced by different promotional focuses and brand images. Other factors play a role in the remaining 36.6% of decisions to purchase Umrah packages at Al-Azhar Bukittinggi travel.